The Lentil Botany, Production and Uses - Erskine, William (CABI, 2014)
The lentil (Lens culinarisMedikus subsp. culinaris) is a lens-shaped grain legume well known as a nutritious food. It grows as an annual bushy leguminous plant typically 20–45 cm tall, which produces many small purseshaped pods containing one to two seeds each. The morphology of the crop is detailed by Saxena (Chapter 4, this volume). Lentil seed is a rich source of protein, minerals (K, P, Fe, Zn) and vitamins for human nutrition (Bhatty, 1988). Furthermore, because of its high lysine and tryptophane content, its consumption with wheat or rice provides a balance in essential amino acids for human nutrition. Lentil straw is also a valued animal feed (Erskine et al., 1990). Lentils were among the earliest of humankind’s plant domesticates (einkorn and emmer wheats, barley, pea, flax and lentil) and are associated with the start of the ‘agricultural revolution’ in the Near East (see Cubero et al., Chapter 3, this volume). The crop was part of the assemblage of neareastern grains that spread across the Old World. It is now produced across the dry areas of the globe and, in the Old World, from Bangladesh in the east to Morocco in the west, and from Russia in the north to Ethiopia in the south. The adaptation of the crop is discussed by Materne and Siddique (Chapter 5, this volume).